STUDY LITERATURE REVIEW FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI REMAJA PUTRI - Tria Nopi Herdiani; Venty HS Manujung; Violita Siska Mutiara (STIKes CHMK, 2021)
The cause of nutritional problems in young women can be caused by a strict diet (which causes adolescents to not get a balanced and nutritious diet) and poor eating habits. This study aims to determine the factors associated with the nutritional status of adolescent girls in 2020. This study uses the literature review method by using the inclusion and exclusion criteria. Keywords used in this literature search include: